2021
DOI: 10.3390/ijerph18031013
|View full text |Cite
|
Sign up to set email alerts
|

Improving Uptake and Sustainability of Sanitation Interventions in Timor-Leste: A Case Study

Abstract: Open defecation (OD) is still a significant public health challenge worldwide. In Timor-Leste, where an estimated 20% of the population practiced OD in 2017, increasing access and use of improved sanitation facilities is a government priority. Community-led total sanitation (CLTS) has become a popular strategy to end OD since its inception in 2000, but evidence on the uptake of CLTS and related interventions and the long-term sustainability of OD-free (ODF) communities is limited. This study utilized a mixed-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
0
4
1
Order By: Relevance
“…This is because most of the respondents were married thus probably having children which could increase the number of household members. The findings were in opposition to a study carried out in Timor-Leste, which found that most households with more than two members did not adopt CLTS (Clarke et al, 2021). Statistics show a strong correlation between the size of the household and the uptake of CLTS.…”
Section: 68%contrasting
confidence: 95%
“…This is because most of the respondents were married thus probably having children which could increase the number of household members. The findings were in opposition to a study carried out in Timor-Leste, which found that most households with more than two members did not adopt CLTS (Clarke et al, 2021). Statistics show a strong correlation between the size of the household and the uptake of CLTS.…”
Section: 68%contrasting
confidence: 95%
“…The literature also supports that there are several programmatic factors that can lead to increased sustainability, which include frequent personal contact with health promoters and accountability over a period of time, 23 having an enabling environment with market access to latrine products, 26, 29, 30 follow-up monitoring, 26, 30-32 social cohesion and social capital among community members, 33 effective community leadership and political will, 31-33 civic pride, 30 access to sanitation markets and hardware, and sustained behavioral change. 31, 33 One possible contributor to the high sustainability we observed in many countries may be that the SSH4A approach is an integrated, multi-dimensional approach with the aim that these different dimensions of the intervention might address the unique sanitation barriers (or enablers) in program areas with different contexts.…”
Section: Discussionmentioning
confidence: 89%
“…Several studies have reported that factors can lead to increased sustainability, including frequent personal contact with health promoters and accountability over a period of time, 23 an enabling environment with market access to latrine products, 30,34,35 follow-up monitoring, 30,[35][36][37] social cohesion and social capital among community members, 38 effective community leadership and political will, [36][37][38] civic pride, 35 access to sanitation markets and hardware, and sustained behavioral change. 36,38 One possible contributor to the high sustainability we observed in many countries may be that the SSH4A approach is an integrated, multidimensional approach with the aim that these different dimensions of the intervention might address the unique sanitation barriers (or enablers) in program areas with different contexts.…”
Section: Discussionmentioning
confidence: 99%